2017
DOI: 10.1111/vru.12480
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thoracic Ultrasonography and Radiography for the Detection of Induced Small Volume Pneumothorax in the Horse

Abstract: Small volume pneumothorax can be challenging to diagnose in horses. The current standard method for diagnosis is standing thoracic radiography. We hypothesized that thoracic ultrasonography would be more sensitive. Objectives of this prospective, experimental study were to describe a thoracic ultrasound method for detection of small volume pneumothorax in horses and to compare results of radiography and ultrasound in a sample of horses with induced small volume pneumothorax. Six mature healthy horses were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The only direct comparison to date between thoracic radiography and ultrasonography in adult horses evaluated 6 horses in which small-volume pneumothorax was experimentally induced. In that study, the diagnostic sensitivity of M-mode (84%) and 2D-mode (80%) TUS was significantly higher ( p = 0.02 and 0.04, respectively) than thoracic radiography (48%) ( 8 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The only direct comparison to date between thoracic radiography and ultrasonography in adult horses evaluated 6 horses in which small-volume pneumothorax was experimentally induced. In that study, the diagnostic sensitivity of M-mode (84%) and 2D-mode (80%) TUS was significantly higher ( p = 0.02 and 0.04, respectively) than thoracic radiography (48%) ( 8 ).…”
Section: Discussionmentioning
confidence: 76%
“…Thoracic ultrasonography in human and small animal medicine is comparable in sensitivity to radiography and computed tomography (CT) for the diagnosis of pneumonia, pulmonary edema, pneumothorax and pulmonary contusions (2)(3)(4)(5)(6). While there have been direct comparisons between the sensitivity of TUS and radiography in the identification of Rhodococcus equi pneumonia in foals and pneumothorax in the adult horse, the two modalities have not been compared for their diagnostic accuracy in bacterial pneumonia in adult horse (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the most common diagnostic modalities for detecting pneumothorax and pneumoperitoneum are ultrasound and radiography (Boy & Sweeney, 2000;Kim et al, 2014). An experimental study by Partlow et al (2017) found that ultrasound (2D and M-mode) is more sensitive than radiography for the detection of small volume induced-pneumothorax in horses.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study by Partlow et al. ( 2017 ) found that ultrasound (2D and M‐mode) is more sensitive than radiography for the detection of small volume induced‐pneumothorax in horses.…”
Section: Discussionmentioning
confidence: 99%
“…In this prospective, experimental study Jessica Partlow and colleagues compared the results of thoracic ultrasonography and radiography for the detection of induced small volume pneumothorax .…”
Section: Detection Of Pneumothoraxmentioning
confidence: 99%